An Experimental Design to Compare Software Requirements Prioritization Techniques - Balsam, A. Mustafa; Azlina, Zainuddin (2014)
Software products are getting increasingly complex described by a large number of requirements that characterize the user needs. In most cases, not all requirements can usually be met with available time and resource contraints; therefore, taking correct decisions about which requirements to implement in a release is crucial as the wrong decision from requirements engineers results in implementation of the false requirements, which lead to failureof project or product in the market. Although much research is done on requirements prioritization techniques, but studies in the area pointed out that when investigating the research made withhin the area, there seems to be little evidence regarding which approach is better than others and in what situations and environments. This paper presents an initial design of a controlled experiment to compare three prioritization methods. The goal of this experiment is to investigate which technique is better in terms of time comsumption, accuracy, and ease of use. The experiment will be conducted in an academic context in Malaysian university.